Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/pin.13099
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the distribution of tumor‐infiltrating CD8+ T cells and FOXP3+ T cells between micronodular thymoma with lymphoid stroma and micronodular thymic carcinoma with lymphoid stroma

Abstract: Micronodular thymoma with lymphoid stroma (MNT) is a rare thymic epithelial neoplasm subtype characterized by a micronodular tumor cell growth pattern and abundant lymphoid stroma. Micronodular thymic carcinoma with lymphoid stroma (MNCA) is considered as a malignant counterpart of MNT and exhibits a growth pattern similar to that of MNT but has histologic features reminiscent of thymic squamous cell carcinoma, such as cytologic atypia and CD5 and CD117 immunoexpression. Although both MNT and MNCA are characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…MNT with lymphoid stroma was originally described by Suster and Moran 1 as a characteristic of multiple micronodular thymoma epithelial cell nests with abundant B cell stroma, often with lymphoid follicles. Interestingly, several variations have been added to the concept of micronodular thymic neoplasm with lymphoid stroma; epithelial components varied from thymoma to thymic carcinoma, and lymphoid stroma was also associated with T cells 2–6 . The thymic tumor was composed of AE1/AE3 anticytokeratin cocktail positive epithelial cells, which showed autonomous growth, whereas the lymphoid stroma consisted of T cells, which declined in number, due to apoptosis, as a consequence of absent epithelial cell nests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MNT with lymphoid stroma was originally described by Suster and Moran 1 as a characteristic of multiple micronodular thymoma epithelial cell nests with abundant B cell stroma, often with lymphoid follicles. Interestingly, several variations have been added to the concept of micronodular thymic neoplasm with lymphoid stroma; epithelial components varied from thymoma to thymic carcinoma, and lymphoid stroma was also associated with T cells 2–6 . The thymic tumor was composed of AE1/AE3 anticytokeratin cocktail positive epithelial cells, which showed autonomous growth, whereas the lymphoid stroma consisted of T cells, which declined in number, due to apoptosis, as a consequence of absent epithelial cell nests.…”
Section: Discussionmentioning
confidence: 99%
“…MNT was first reported by Suster and Moran, 1 and since then accumulated case reports have indicated that this tumor represents a spectrum of micronodular thymic epithelial tumor cell proliferations, varying from micronodular thymoma to thymic carcinoma with lymphoid stroma and with intratumorous lymphoma. [2][3][4][5][6] The biological properties of thymic epithelial cells, including their ability to attract and harbor lymphocytes to promote lymphocyte development, 7 might be related to the lymphoid stroma formation of micronodular thymic neoplasm. However, the pathobiological and molecular mechanisms (e.g., humoral factor pathway) underlying abundant lymphoid stroma formation in micronodular thymic neoplasm remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTC is a rare subtype of thymic carcinoma, and the histological characteristic of MTC or MT is the formation of tumor nodules accompanied by lymphoid stroma, unlike other common thymomas [1]. To date, 23 cases of MTC have been reported (Table 1) [2][3][4][5][6][7][8][9]. The mean age of the patients was 62.9 years (range 42-82 years) and the mean tumor size was 3.7 cm (range 1.1-10 cm).…”
Section: Discussionmentioning
confidence: 99%
“…MT, which was rst described in 1999 by Suster et al, is a rare subtype of thymoma, accounting for 5% of thymomas, and comprising neoplastic epithelial nests and surrounding hyperplastic lymphoid tissue containing a germinal center [2]. Since MT and MTC share a similar morphology, MTC is considered a malignant form of MT; there have been a few cases of malignant transformation from MT to MTC [2][3][4][5][6][7][8][9]. Herein, we describe a case of MTC accompanied by a benign histological component of thymoma and review the literature.…”
Section: Introductionmentioning
confidence: 99%